Banco para compartilhamento de imagens do INSCER : estudos de FMRI e sMRI de crianças, adolescentes e adultos brasileiros - Kotoski, Aline (2021)
The idea of data-sharing for neuroimaging data has become increasingly present, as studies with structural and functional magnetic resonance data depend on funding and vast knowledge in data acquisition (Milham et al., 2018). In addition, some populations are difficult to access, such as children in their early years of education. We present an open dataset of fMRI and sMRI imaging research carried out at the Brain Institute (BraIns), Pontifical Catholic University of Rio Grande do Sul, Brazil. The dataset includes fMRI and sMRI data from brain imaging studies of studies of children with developmental dyslexia and neurotypical readers, of pre-adolescents and exposure to violence, of bilingual speakers of a minority language, and of young adults and use of social media. We also present behavioral, demographic and evaluation data including I.Q., socioeconomic status, an internet addiction test and academic evaluations. The objective is to provide access to brain imaging studies of Brazilian children, youths and adults and, also, to establish the structure to continue to build on and provide access to brain imaging data. The data are from an underrepresented population in fMRI and sMRI studies. We carried out proper anonymization and quality control of the sMRI and fMRI data and provide the description of data, procedures and analyses.